Choroidal γδ T cells in protection against retinal pigment epithelium and retinal injury. Issue 11 (20th July 2017) - Zhao, Zhenyang; Liang, Yuejin; Liu, Yin; Xu, Pei; Flamme‐Wiese, Miles J.; Sun, Deming; Sun, Jiaren; Mullins, Robert F.; Chen, Yan; Cai, Jiyang
Abstract : γδ T cells located near the epithelial barrier are integral components of local inflammatory and innate immune responses. We have previously reported the presence of choroidal γδ T cells in a model of chronic degeneration of the retinal pigment epithelium (RPE). The goals of the current study were to further define the functions of choroidal γδ T cells and to explore the underlying mechanisms of their action. Our data demonstrate that choroidal γδ T cells are activated by RPE injury in response to NaIO3 treatment, and that they express genes that encode immunosuppressive cytokines, such as IL‐4 and IL‐10. γδ‐T‐cell–deficient mice developed profound RPE and retinal damage at doses that caused minimal effects in wild‐type mice, and adoptive transfer of γδ Tcells prevented sensitization. Intravitreal injection of IL‐4 and IL‐10 ameliorated RPE toxicity that was induced by NaIO3 . Ex vivo coculture of γδ T cells with RPE explants activated the production of anti‐inflammatory cytokines via an aryl hydrocarbon receptor (AhR)‐dependent mechanism. AhR deficiency abolished the protective effects of γδ Tcells after adoptive transfer. Collectively, these findings define important roles for choroid γδ T cells in maintaining tissue homeostasis in the outer retina.—Zhao, Z., Liang, Y., Liu, Y., Xu, P., Flamme‐Wiese, M. J., Sun, D., Sun, J., Mullins, R. F., Chen, Y., Cai, J. Choroidal γδ T cells in protection against retinal pigment epithelium and retinal injury. FASEB J. 31, 4903–4916 (2017). www.fasebj.org